Plywood made from plasma-treated veneers: Shear strength after shrinkage-swelling stress. (October 2017) - Wascher, R.; Avramidis, G.; Kühn, C.; Militz, H.; Viöl, W.
Abstract: Thermally modified and unmodified beech veneers in untreated and plasma-treated state were immersed in melamine solution at different concentrations. The plasma pre-treated veneers exhibited significantly higher melamine loads than the untreated veneers at equal impregnation duration. Subsequently the veneers were manufactured into 5-layer plywood boards; the plywood samples then underwent an extreme testing procedure based on DIN-EN 314-1/2 in order to proof the bonding quality by means of shear strength. The plywood boards made of plasma pre-treated veneers exhibited up to 2.7-fold improvement in shear strength compared to plywood made of untreated veneers. Results differed markedly based on material (unmodified/thermally modified veneer) and concentration of melamine solution.